Ascertaining the link between dengue and climatic conditions - Arcenas, Agustin (2016)
I examine climate-change related factors affecting the incidence of dengue in the Philippines. Dengue is estimated to cost hundreds of millions of dollars in the Philippines and worldwide in terms of treatment, surveillance and control, lost income, and other indirect costs per year. The disease is a burden especially for the poor, who are less able to access funds for treatment and are more heavily affected by the loss in income due to illness.

Econometric results show that temperature, precipitation, and the incidence of La Niña contribute significantly to the cases of dengue in the Philippines, since these conditions enhance the breeding, growth, and development of Aedes aegypti, the dengue carrying mosquito. Better household sanitation practices are also found to reduce dengue cases, indicating that investments to enhance the public’s adoption of hygienic and other health practices lessen the transmission of the disease. Such results are consistent with the findings of studies regarding dengue in other parts of the world and contribute to the growing awareness about the health impacts of climate change. This study provides policy makers with additional guidance as climate change in the region becomes more pronounced.
Keywords: Dengue -- Economic aspects